Compliant flooring to prevent fall-related injuries: a scoping review protocol. Issue 8 (16th August 2016) - Lachance, Chantelle C; Jurkowski, Michal P; Dymarz, Ania C; Mackey, Dawn C
Abstract : Introduction: Fall-related injuries can have serious consequences for older adults, including increased risk of dependence in daily activities and mortality. Compliant flooring is a passive intervention that may reduce the incidence and severity of fall-related injuries in healthcare settings, including acute and long-term care, but few sites have implemented compliant flooring, in part because synthesised evidence about key performance aspects has not been available. Methods and analysis: We will conduct a scoping review to address the question: what is presented about the biomechanical efficacy, clinical effectiveness, cost-effectiveness, and workplace safety associated with compliant flooring systems that aim to prevent fall-related injuries? We will conduct a comprehensive and systematic literature search of academic databases (AgeLine, CINAHL, EBM Reviews, MEDLINE (Ovid), SportDiscus and Web of Science) and grey literature (clinical trial registries, theses/dissertations, abstracts/conference proceedings and relevant websites). 2 team members will independently screen records (first titles and abstracts, then full text) and extract data from included records. Numerical and narrative analyses will be presented by theme (biomechanical efficacy, clinical effectiveness, cost-effectiveness, workplace safety). Ethics and dissemination: This scoping review responds to the information needs of healthcare decision-makers tasked with preventing fall-related injuries. This review will summarise evidence about compliant flooring as a potential intervention for preventing fall-related injuries in older adults and identify gaps in evidence and new avenues for research. Results will be especially useful in long-term care, but also applicable in acute care, assisted living and home care. We will disseminate the review's findings via open-access publications, conference presentations, a webinar, a Stakeholder Symposium and a Knowledge-to-Action Report.